2016
DOI: 10.1101/056838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marine Ecosystems as Complex Adaptive Systems: Emergent Patterns, Critical Transitions, and Public Goods

Abstract: Complex adaptive systems provide a unified framework for explaining ecosystem phenomena. Three ubiquitous features of ecosystems that arise from this framework are emergent patterns, critical transitions, and cooperative behavior. Focusing on marine ecosystems, we present numerous examples of each phenomenon, using the theory of complex adaptive systems to explain the universal features and common mechanisms shared by disparate ecosystems, as well as the important differences. Marine ecosystems provide importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 196 publications
(237 reference statements)
0
14
0
Order By: Relevance
“…Primary production, which represents phytoplankton biomass and growth rates , is sensitive to environmental change (Wu, He, et al, 2014). It is mainly regulated by various factors that include incident irradiance (Lewis, 2011;Wang et al, 2015), ice cover (Lewis, 2011), nonalgal light attenuation (Deng et al, 2017;Wu, Lai, Zhang, Cai, & Chen, 2014), mixing depth , temperature (Liang et al, 2017), and the nutrient supply (Browning et al, 2017;Dou, Tang, Yang, & Wang, 2011;Hagstrom & Levin, 2017;Ke, Tan, Ma, Huang, & Wang, 2014;Li, Ge, Wang, Zhou, & Hu, 2016;Liu et al, 2015;Wang et al, 2015;Wilkerson, Dugdale, Parker, Blaser, & Pimenta, 2015;Yin, Liu, & Harrison, 2017), especially for nutrient inputs that have a significant effect on phytoplankton growth and development as well as the biogeochemical cycles of watersheds (Browning et al, 2017;Li et al, 2016;Moore et al, 2013;Wen et al, 2012). In addition, nutrient inputs, particularly nitrogen (N) and phosphorus (P), to freshwater ecosystems have continued to increase due to progressively increasing anthropogenic activities resulting from rising populations, broadening economic development, and the greater demand for food and energy production in recent years (Cao, Wang, Liao, Sun, & Huang, 2016;Wilkerson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary production, which represents phytoplankton biomass and growth rates , is sensitive to environmental change (Wu, He, et al, 2014). It is mainly regulated by various factors that include incident irradiance (Lewis, 2011;Wang et al, 2015), ice cover (Lewis, 2011), nonalgal light attenuation (Deng et al, 2017;Wu, Lai, Zhang, Cai, & Chen, 2014), mixing depth , temperature (Liang et al, 2017), and the nutrient supply (Browning et al, 2017;Dou, Tang, Yang, & Wang, 2011;Hagstrom & Levin, 2017;Ke, Tan, Ma, Huang, & Wang, 2014;Li, Ge, Wang, Zhou, & Hu, 2016;Liu et al, 2015;Wang et al, 2015;Wilkerson, Dugdale, Parker, Blaser, & Pimenta, 2015;Yin, Liu, & Harrison, 2017), especially for nutrient inputs that have a significant effect on phytoplankton growth and development as well as the biogeochemical cycles of watersheds (Browning et al, 2017;Li et al, 2016;Moore et al, 2013;Wen et al, 2012). In addition, nutrient inputs, particularly nitrogen (N) and phosphorus (P), to freshwater ecosystems have continued to increase due to progressively increasing anthropogenic activities resulting from rising populations, broadening economic development, and the greater demand for food and energy production in recent years (Cao, Wang, Liao, Sun, & Huang, 2016;Wilkerson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have addressed the effects of nutrients (N, P, C, iron [Fe], etc. ), as it relates to both concentration or structure, on phytoplankton growth (Browning et al, 2017;Dou et al, 2011;Hagstrom & Levin, 2017;Ke et al, 2014;Li et al, 2016;Liu et al, 2015;Wang et al, 2015;Wilkerson et al, 2015;Yin et al, 2017). Browning et al (2017) reported that the different ratios related to nutrient concentration and structure could alter species composition and phytoplankton growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, whereas traditional natural resource management had taken an anthropocentric approach, with nature existing to serve human needs, EBM takes a bio/eco-centric perspective, focusing on key ecological, management and social aspects, such as: the emphasis of ecological protection as an essential component of sustainability; the recognition of humans as key elements of the ecosystem; the acknowledgment of complex linkages between ecosystems and social and economic components; the need to consider crossscale interactions; the need to improve management through systematic evaluation, Table 1.1: Key features and behaviours of marine social-ecological systems as CAS (adapted from van der Lei et al, 2009 andGrus et al, 2010; based on Hughes et al, 2005, Halpern et al 2008, Perry et al, 2010and Hagstrom and Levin, 2016.…”
Section: Scientific Research On Marine Complex Adaptive Systemsmentioning
confidence: 99%
“…at microbial level, such as the Sheldon Spectrum 1 and Margalef's Mandala 2 (Hagstrom and Levin, 2016) Openness Social-ecological systems are delimited by open spatial or functional boundaries…”
Section: Social-ecological Systemsmentioning
confidence: 99%